2003
DOI: 10.1128/aem.69.4.1898-1903.2003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Particles on the Recovery of Cryptosporidium Oocysts from Source Water Samples of Various Turbidities

Abstract: Cryptosporidium parvum can be found in both source and drinking water and has been reported to cause serious waterborne outbreaks which threaten public health safety. The U.S. Environmental Protection Agency has developed method 1622 for detection of Cryptosporidium oocysts present in water. Method 1622 involves four key processing steps: filtration, immunomagnetic separation (IMS), fluorescent-antibody (FA) staining, and microscopic evaluation. The individual performance of each of these four steps was evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
1
7

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 14 publications
3
29
1
7
Order By: Relevance
“…Using direct microscopy, settling columns, and batch experiments, we demonstrated that C. parvum oocysts generally associate with suspended sediments under a wide range of background water chemistry conditions. These findings are congruent with the results of Feng et al and Medema et al (9,22), who also demonstrated through batch experiments that C. parvum oocysts associate with suspended particles. In our experiments, oocysts attached to a variety of negatively charged suspended sediments.…”
Section: Discussionsupporting
confidence: 83%
“…Using direct microscopy, settling columns, and batch experiments, we demonstrated that C. parvum oocysts generally associate with suspended sediments under a wide range of background water chemistry conditions. These findings are congruent with the results of Feng et al and Medema et al (9,22), who also demonstrated through batch experiments that C. parvum oocysts associate with suspended particles. In our experiments, oocysts attached to a variety of negatively charged suspended sediments.…”
Section: Discussionsupporting
confidence: 83%
“…The recovery rates, however, were lower than the rates reported in other studies (1,3,17). Filtration procedures, which have been shown to result in a decrease of the recovery rate by Feng et al (3), were not performed in the present study. We evaluated the IMS sample preparation procedure by allowing the oocysts to contact suspended solids concentrated from river water.…”
Section: Discussioncontrasting
confidence: 54%
“…The cartridge/ foam filter and immunomagnetic separation, for their quickly filtration and specificity, were recommended for Cryptosporidium detection by the method 1623 of the USEPA, but their high cost makes it difficult to conduct environmental survey in large scale. Meanwhile, many studies have noted declines in Cryptosporidium and Giardia recovery levels to near or below minimum acceptable levels in waters of high turbidity or high total suspended solid (Krometis et al 2009;Feng et al 2003;Hu et al 2004). It is possible that Cryptosporidium oocysts, which could be adhered to particles, were still retained in the filter after elution process (Feng et al 2003).…”
Section: Initial Precision and Recovery Of Cryptosporidium Parvum Oocmentioning
confidence: 99%
“…Meanwhile, many studies have noted declines in Cryptosporidium and Giardia recovery levels to near or below minimum acceptable levels in waters of high turbidity or high total suspended solid (Krometis et al 2009;Feng et al 2003;Hu et al 2004). It is possible that Cryptosporidium oocysts, which could be adhered to particles, were still retained in the filter after elution process (Feng et al 2003). So in this study, we employed a concentration and purification method adopted by Japan including cellulose ester membrane filtration, acetone dissolution, and Percoll-sucrose flotation in succession (Japanese Ministry of Health Labor and Welfare 2007).…”
Section: Initial Precision and Recovery Of Cryptosporidium Parvum Oocmentioning
confidence: 99%